Composite film and preparation method thereof, and luminescent device and preparation method thereof
By setting multiple pixel regions on the substrate and forming electric fields with different electric field intensities in different regions, quantum dot materials are deposited in the corresponding regions during the electrophoretic deposition process, the problem of long and complex time of quantum dot film layer preparation process in the prior art is solved, and a faster and simplified preparation process is achieved.
Patent Information
- Application Number
- CN202311281714.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
The existing quantum dot film layer preparation process has a long processing time and a complex processing process.
By using the preparation method of a composite film, by setting the first pixel region and the second pixel region on the substrate, and place the substrate and the metal substrate into the mixed solution, by forming an electric field of different electric field strengths between different pixel regions and the metal substrate, the material in the mixed solution is deposited in the corresponding region, forming a composite film of different thicknesses.
The processing time of composite films is shortened, manufacturing complexity and production costs are reduced, and the processing technology of quantum dot light emitting devices is simplified.
Smart Images

Figure CN119730653A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of display technology, and more specifically, to a method for preparing a composite film, a composite film, a light-emitting device, and a method for preparing a light-emitting device. Background Art
[0002] Quantum dots (QD) are considered to be a promising luminescent material due to their high luminescence efficiency, flexible and adjustable luminescence wavelength, narrow luminescence half-width, and low-cost solution preparation.
[0003] At present, electrophoretic deposition can be used to prepare quantum dot films. It mainly uses the method of using charged quantum dot materials to move in a specific direction under the action of an electric field and selectively deposit on a specific electrode to prepare quantum dot films. It is convenient and fast, and can prepare quantum dot films on a large area. It has become an important research direction for the development of the display field. Among them, the immersion method is a common method for preparing quantum dot films by electrophoretic deposition. The obtained quantum dot films have good uniformity. However, when the conventional immersion method is used to prepare full-color (red, green, blue) QLED devices, multiple immersions are required to complete the preparation of multiple quantum dot film layers (red, green, blue), which increases production costs and processing time, and the processing technology is complicated. Summary of the invention
[0004] The technical problem to be solved by the embodiments of the present application is that the existing quantum dot film preparation process has a long processing time and a complex processing process.
[0005] In order to solve the above technical problems, the present application provides a method for preparing a composite film, which adopts the following technical solution:
[0006] A method for preparing a composite film comprises the following steps:
[0007] Providing a mixed solution including a first material solution and a second material solution;
[0008] Providing a substrate and a metal substrate, placing the substrate and the metal substrate in the mixed quantum dot solution, wherein the substrate is provided with a first pixel region and a second pixel region;
[0009] A first electric field is set between the first pixel area and the metal substrate, and a second electric field is set between the second pixel area and the metal substrate so that the first material and the second material in the mixed solution are deposited in the first pixel area and the second pixel area to form the composite film, wherein the thickness of the composite film located in the first pixel area is different from that of the composite film located in the second pixel area.
[0010] Furthermore, the electric field strength of the first electric field is greater than the electric field strength of the second electric field.
[0011] Furthermore, the mixed solution also includes a third material solution, the volume of the third material solution is greater than the volume of the first material solution, and the volume of the third material solution is greater than the volume of the second material solution.
[0012] Further, the first material solution includes a first material and a solvent, the second material solution includes a second material and a solvent, and the third material solution includes a third material and a solvent, wherein the first material, the second material, and the third material are luminescent materials;
[0013] The first material solution, the second material solution and the third material solution are all prepared by the following steps:
[0014] Providing a luminescent material and a solvent, wherein the polarity of the solvent is greater than 3 Debye;
[0015] The luminescent material is mixed with a solvent to form a quantum dot solution.
[0016] Furthermore, the luminescent material includes quantum dots and quantum dot ligands, and the luminescent material is prepared by the following steps:
[0017] Mixing the quantum dot ligand and the quantum dot according to a first mixing mass ratio to form a first luminescent material;
[0018] Mixing the quantum dot ligand and the quantum dot according to a second mixing mass ratio to form a second luminescent material;
[0019] Mixing the quantum dot ligand and the quantum dot according to a third mixing mass ratio to form a third luminescent material;
[0020] The first material solution, the second material solution and the third material solution are all formed by mixing quantum dot ligands and quantum dots of the same material with a solvent.
[0021] Further, the first mixed mass ratio ranges from (3 to 10.3): (5 to 8.7); and / or
[0022] The second mixing mass ratio is in the range of (3.5-4.1): (5-5.6); and / or
[0023] The third mixing mass ratio ranges from (1.4 to 4): (3.9 to 5).
[0024] Furthermore, the first mixing mass ratio is 10.3:8.7, the second mixing mass ratio is 4.1:5.6, and the third mixing mass ratio is 1.4:3.9.
[0025] Furthermore, the luminescent material includes quantum dots and quantum dot ligands, and the luminescent material is prepared by the following steps:
[0026] Mixing a first quantum dot ligand with the quantum dots according to a fourth mixing mass ratio to form a first light-emitting material, wherein the material of the first quantum dot ligand is selected from one of a hydroxyl ligand, a thiol ligand and an acid ligand;
[0027] Mixing a second quantum dot ligand with the quantum dots according to a fourth mixing mass ratio to form a second light-emitting material, wherein the material of the second quantum dot ligand is selected from one of a hydroxyl ligand, a thiol ligand and an acid ligand;
[0028] Mixing a third quantum dot ligand with the quantum dots according to a fourth mixing mass ratio to form a third light-emitting material, wherein the material of the third quantum dot ligand is selected from one of a hydroxyl ligand, a thiol ligand and an acid ligand;
[0029] The first material solution, the second material solution and the third material solution are respectively formed by mixing quantum dot ligands and quantum dots of different materials with the solvent.
[0030] Furthermore, the fourth mixing mass ratio is in the range of (3-5):5.
[0031] Further, the luminescent material is a quantum dot luminescent material, and the quantum dot luminescent material includes at least one of a single structure quantum dot and a core-shell structure quantum dot; the material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot are respectively selected from at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSe At least one of Te, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnT e, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, and the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, A At least one of InNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2;
[0032] The quantum dot ligands include at least one of hydroxyl ligands, acid ligands, thiol ligands, amine ligands, (oxygen) phosphine ligands, phospholipids, phospholipids, polyvinyl pyridine, etc. The hydroxyl ligands include at least one of polyethylene glycol, polyethylene glycol-hydroxyl, glyceride, pentaerythritol ester and sorbitan ester; the acid ligands include at least one of deca-acid, undecylenic acid, tetradecanoic acid, oleic acid and stearic acid; the thiol ligands include at least one of n-octyl mercaptan, octadecyl mercaptan, dodecyl mercaptan and octadecyl mercaptan; the amine ligands include one or more of oleylamine, octadecylamine and octadecylamine; the (oxygen) phosphine ligands include at least one of trioctylphosphine and trioctylphosphine oxide; and / or
[0033] The luminescent material is an organic luminescent material, and the organic luminescent material includes at least one of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-C2,N)iridium(III), 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives; and / or
[0034] The material of the solvent may be selected from at least one of water, alcohol compounds, ether compounds, ester compounds and alkane compounds.
[0035] Furthermore, after forming a first electric field between the first pixel region and the metal substrate and forming a second electric field between the second pixel region and the metal substrate so that the light-emitting material in the mixed solution is deposited on the first pixel region and the second pixel region respectively, the following steps are also included:
[0036] taking the substrate out of the mixed solution, wherein the substrate remains in a conductive state with a power source;
[0037] placing the substrate into a solvent for immersion;
[0038] The soaked substrate is dried to form a composite film.
[0039] The present application also provides a composite film, which adopts the following technical solution:
[0040] A composite film, characterized in that it is prepared by the composite film preparation method as described above, comprising:
[0041] Providing a mixed solution comprising a first material and a second material;
[0042] Providing a substrate and a metal substrate, placing the substrate and the metal substrate in the mixed solution, wherein the substrate is provided with a first pixel region and a second pixel region;
[0043] A first electric field is set between the first pixel area and the metal substrate to deposit the first material in the first pixel area, and a second electric field is set between the second pixel area and the metal substrate to deposit the second material in the second pixel area to form the composite film.
[0044] The composite film located in the first pixel region has a different thickness from the composite film located in the second pixel region.
[0045] The present application also provides a light emitting device, which adopts the following technical solution:
[0046] A light-emitting device comprises an anode layer, a hole functional layer, a light-emitting layer, an electron functional layer and a cathode layer which are stacked;
[0047] Wherein, the light-emitting layer is prepared by the composite film as described above or by the composite film preparation method as described above. Further, the material of the anode layer and / or cathode layer includes one or more of metal, carbon material and metal oxide, the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes doped or undoped metal oxide, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or includes a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or
[0048] The hole functional layer includes a hole transport layer and / or a hole injection layer, and the material of the hole transport layer and / or the hole injection layer includes at least one of TFB, CuPc, PVK, Poly-TPD, PFB, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS, TAPC, MCC, F4-TCNQ, HATCN, 4,4',4'-tris(N-3-methylphenyl-Nphenylamino)triphenylamine, polyaniline, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped graphene, undoped graphene and C60; and / or
[0049] The electronic functional layer includes an electron transport layer and / or an electron injection layer, and the materials of the electron transport layer and / or the electron injection layer include inorganic materials and / or organic materials; the inorganic material is selected from one or more of doped or undoped zinc oxide, barium oxide, aluminum oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, aluminum zinc oxide, manganese zinc oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped elements include one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material includes at least one of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, hydroxyquinoline compounds, polythiophene compounds, perylene imide compounds, and fullerene compounds.
[0050] The present invention also provides a method for preparing a light-emitting device, comprising the following steps:
[0051] A method for preparing a light-emitting device, for preparing the light-emitting device as described above, comprises the following steps:
[0052] providing an anode layer;
[0053] preparing a hole functional layer on the anode layer;
[0054] Preparing a light-emitting layer on the hole functional layer by the above-mentioned composite thin film preparation method;
[0055] preparing an electronic functional layer on the light-emitting layer;
[0056] A cathode layer is formed on the electronic functional layer.
[0057] Compared with the prior art, the embodiments of the present application have the following beneficial effects:
[0058] The present application sets a first pixel area and a second pixel area on a substrate, immerses the substrate and the metal substrate in a mixed solution containing a first material solution and a second material solution, and forms electric fields with different electric field strengths between different pixel areas and the metal substrate, so that composite films of different thicknesses are simultaneously formed on corresponding areas of the substrate. There is no need to perform multiple electrophoresis on the substrate, thereby shortening the processing time of the composite film and reducing the manufacturing complexity and production cost of the composite film. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] In order to more clearly illustrate the scheme of the present application, a brief introduction is given below to the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0060] Figure 1 is a flow chart of a method for preparing a composite film according to an embodiment of the present application;
[0061] Figure 2 is a flow chart of a method for preparing a mixed solution according to an embodiment of the present application;
[0062] Figure 3 This is a working principle diagram of preparing a composite film by electrophoretic deposition in an embodiment of the present application;
[0063] Figure 4 is a schematic structural diagram of a light-emitting device according to an embodiment of the present application;
[0064] Reference numerals:
[0065] 1. Substrate; 11. First pixel region; 12. Second pixel region; 13. Third pixel region; 21. First composite film; 22. Second composite film; 23. Third composite film; 3. Anode layer; 4. Hole functional layer; 41. Hole injection layer; 42. Hole transport layer; 5. Electron transport layer; 6. Cathode layer; 7. Metal substrate. DETAILED DESCRIPTION
[0066] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of this application; the terms used in the specification of the application herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned drawings are intended to cover non-exclusive inclusions. The terms "first", "second", etc. in the specification and claims of this application or the above-mentioned drawings are used to distinguish different objects, not to describe a specific order.
[0067] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0068] Embodiment of the method for preparing the composite film of the present application
[0069] See also Figure 1 As shown, the embodiment of the present application provides a method for preparing a composite film, comprising the following steps:
[0070] Step S10, providing a mixed solution including a first material solution and a second material solution.
[0071] Step S20, providing a substrate and a metal substrate, placing the substrate and the metal substrate in the mixed solution, wherein a first pixel region and a second pixel region are provided on the substrate.
[0072] Step S30, setting a first electric field between the first pixel area and the metal substrate, and setting a second electric field between the second pixel area and the metal substrate to make the first material and the second material in the mixed solution deposit on the substrate respectively to form the composite film.
[0073] In this embodiment, the composite film located in the first pixel region and the composite film located in the second pixel region have different thicknesses, and the composite film contains both the first material and the second material.
[0074] The present application sets a first pixel area and a second pixel area on a substrate, immerses the substrate and the metal substrate in a mixed solution containing a first material solution and a second material solution, and forms electric fields with different electric field strengths between different pixel areas and the metal substrate, so that composite films of different thicknesses are simultaneously formed on corresponding areas of the substrate. There is no need to perform multiple electrophoresis on the substrate, thereby shortening the processing time of the composite film and reducing the manufacturing complexity and production cost of the composite film.
[0075] In some embodiments, the mixed solution further includes a third material solution, the volume of the third material solution is greater than the volume of the first material solution, and the volume of the third material solution is greater than the volume of the second material solution.
[0076] The first material solution includes a first material and a solvent, the second material solution includes a second material and a solvent, and the third material solution includes a third material and a solvent, wherein the first material, the second material, and the third material are luminescent materials.
[0077] See also Figure 2 As shown, in some embodiments, the first material solution, the second material solution, and the third material solution in step S10 are prepared by the following steps respectively:
[0078] Step S11, providing a luminescent material and a solvent, wherein the polarity of the solvent is greater than 3 Debye.
[0079] In this embodiment, the material solution is a quantum dot solution, the luminescent material includes quantum dots and quantum dot ligands, and the luminescent material is prepared by the following steps:
[0080] The quantum dot ligand and the quantum dots are mixed according to a set mixing mass ratio to form a quantum dot solute, wherein the set mixing mass ratio is in the range of (1 to 10.3): (1 to 20).
[0081] Step S12, dissolving the luminescent material in the solvent to form a quantum dot solution.
[0082] The method for preparing a composite film provided in an embodiment of the present application is performed by dissolving a quantum dot solute in a solvent with a polarity greater than 3 Debye, wherein the solvent provides an ionization environment for the quantum dot solute, so that the quantum dot solute can be ionized in the solvent to realize that the surface of the quantum dots is charged, so that the quantum dot film layer can be subsequently prepared by electrophoresis. In addition, by forming different electric field strengths between different pixel areas and the metal substrate, composite films of different thicknesses are simultaneously formed on corresponding areas of the substrate, without the need to perform multiple electrophoresis on the substrate, thereby shortening the processing time of the composite film and reducing the manufacturing complexity and production cost of the composite film.
[0083] In some embodiments, the quantum dots include at least one of single structure quantum dots and core-shell structure quantum dots;
[0084] In some embodiments, the material of the single structure quantum dot, the core material of the core-shell structure quantum dot, and the shell material of the core-shell structure quantum dot are respectively selected from at least one of the II-VI group compounds, the IV-VI group compounds, the III-V group compounds, and the I-III-VI group compounds, wherein the II-VI group compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS , HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, At least one of SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, wherein the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, At least one of AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2.
[0085] In some embodiments, the quantum dot ligand includes at least one of hydroxyl ligand, acid ligand, thiol ligand, amine ligand, (oxygen) phosphine ligand, phospholipid, soft phosphine, polyvinyl pyridine, etc. The hydroxyl ligand includes at least one of polyethylene glycol, polyethylene glycol-hydroxyl, glyceride, pentaerythritol ester and sorbitan ester; the acid ligand includes at least one of deca-acid, undecylenic acid, tetradecanoic acid, oleic acid and stearic acid; the thiol ligand includes at least one of n-octyl mercaptan, octadecyl mercaptan, dodecyl mercaptan and octadecyl mercaptan; the amine ligand includes one or more of oleylamine, octadecylamine and octadecylamine; the (oxygen) phosphine ligand includes at least one of trioctylphosphine and trioctylphosphine oxide.
[0086] In some embodiments, the material of the solvent can be selected from at least one of water, alcohol compounds, ether compounds, ester compounds and alkane compounds, wherein the solvent can be water, propylene glycol methyl ether acetate (2-Acetoxy-1-Methoxypropane, PGMEA), acetonitrile, dimethyl sulfoxide (DMSO), ethyl acetate, and no limitation is made here.
[0087] In this embodiment, the quantum dots are core-shell structured quantum dots, wherein the core material of the core-shell structured quantum dots is CdSe, the shell material of the core-shell structured quantum dots is ZnS, the material of the quantum dot ligand is polyethylene glycol-hydroxy (PEG-COOH), the polarity of the solvent is greater than 3 Debye, and the material of the solvent is propylene glycol methyl ether acetate (PGMEA). The solvent provides a good ionization environment for the quantum dot solute, and the quantum dot ligand falls off in the solvent, so that the surface of the quantum dot is charged, so that during subsequent electrophoresis, the quantum dots can be deposited on the substrate to form a quantum dot film layer.
[0088] In some embodiments, the first material solution, the second material solution and the third material solution are all formed by mixing quantum dot ligands and quantum dots of the same material and dissolving them in the solvent, wherein the material of the quantum dot ligands is polyethylene glycol-hydroxy (PEG-COOH), the material of the quantum dots is CdSe / ZnS core-shell structure quantum dots, and the material of the solvent is propylene glycol methyl ether acetate (PGMEA).
[0089] In this embodiment, the step of mixing the quantum dot ligand and the quantum dot according to a set mixing mass ratio to form a luminescent material specifically includes the following steps:
[0090] The quantum dot ligand and the quantum dots are mixed according to a first mixing mass ratio to form a first light-emitting material.
[0091] In this embodiment, the first mixed mass ratio ranges from (3 to 10.3): (5 to 8.7). For example, the polyethylene glycol-hydroxyl group (PEG-COOH): CdSe / ZnS core-shell structure quantum dots in the first luminescent material are 3:5, 4:5, 6:6, 8:7, and 10.3:8.7. The electrophoretic mobility during electrophoretic deposition can be appropriately adjusted according to the actual selection and specific needs. In this embodiment, the first mixed mass ratio is preferably 10.3:8.7, and the first luminescent material is a red light quantum dot solute.
[0092] The quantum dot ligand and the quantum dots are mixed according to a second mixing mass ratio to form a second light-emitting material.
[0093] In this embodiment, the second mixed mass ratio ranges from (3.5 to 4.1): (1 to 5.6). For example, the polyethylene glycol-hydroxyl group (PEG-COOH): CdSe / ZnS core-shell structure quantum dots in the second luminescent material are 3.5:5, 4:5, and 4.1:5.6. The electrophoretic mobility during electrophoretic deposition can be appropriately adjusted according to the actual selection and specific needs. In this embodiment, the second mixed mass ratio is preferably 4.1:5.6, and the second luminescent material is a green light quantum dot solute.
[0094] The quantum dot ligand and the quantum dots are mixed according to a third mixing mass ratio to form a third light-emitting material.
[0095] In this embodiment, the third mixing mass ratio ranges from (1.4 to 4): (3.9 to 5). For example, the polyethylene glycol-hydroxyl group (PEG-COOH): CdSe / ZnS core-shell structure quantum dots in the third luminescent material are 1.4:3.9, 2:4, 3.5:5, and 4:5. The electrophoretic mobility during electrophoretic deposition can be appropriately adjusted according to actual conditions and specific needs. In this embodiment, the third mixing mass ratio is preferably 1.4:3.9, and the third luminescent material is a blue light quantum dot solute.
[0096] In the embodiment of the present application, the quantum dot ligand and the quantum dots are mixed in different mixing mass ratios to prepare the first luminescent material, the second luminescent material and the third luminescent material, respectively, so that the surface potentials of the quantum dots after being dissolved in the solvents are different, and thus the electron mobility of the quantum dots under the electric field is also different, so that in the subsequent electrophoresis process, composite films of different thicknesses meeting different optical efficiency requirements can be prepared simultaneously in the first pixel area, the second pixel area and the third pixel area, thereby shortening the processing time of the composite film and reducing the manufacturing complexity and production cost of the composite film.
[0097] Since the electron mobility of quantum dots in the mixed solution is also related to the material of the quantum dot ligands, in other embodiments, the first material solution, the second material solution and the third material solution can also be formed by mixing quantum dot ligands and quantum dots of different materials with the solvent.
[0098] In other embodiments, the step of mixing the quantum dot ligand and the quantum dot according to a set mixing mass ratio to form a luminescent material may further include the following steps:
[0099] The first quantum dot ligand is mixed with the quantum dots according to a fourth mixing mass ratio to form a first light-emitting material.
[0100] Among them, the material of the first quantum dot ligand is selected from one of a hydroxyl ligand, a thiol ligand and an acid ligand; in some embodiments, the hydroxyl ligand includes at least one of polyethylene glycol, polyethylene glycol-hydroxyl, glyceride, pentaerythritol ester and anhydrous sorbitan ester; the acid ligand includes at least one of decadecanoic acid, undecenoic acid, tetradecanoic acid, oleic acid and stearic acid; the thiol ligand includes at least one of n-octyl mercaptan, octadecyl mercaptan, dodecyl mercaptan and octadecyl mercaptan; in this embodiment, the material of the first quantum dot ligand is oleic acid, and the first luminescent material is a red light quantum dot solute.
[0101] The second quantum dot ligand is mixed with the quantum dots according to a fourth mixing mass ratio to form a second light-emitting material.
[0102] Among them, the material of the second quantum dot ligand is selected from one of a hydroxyl ligand, a thiol ligand and an acid ligand; in some embodiments, the hydroxyl ligand includes at least one of polyethylene glycol, polyethylene glycol-hydroxyl, glyceride, pentaerythritol ester and anhydrous sorbitan ester; the acid ligand includes at least one of decadecanoic acid, undecenoic acid, tetradecanoic acid, oleic acid and stearic acid; the thiol ligand includes at least one of n-octyl mercaptan, octadecyl mercaptan, dodecyl mercaptan and octadecyl mercaptan; in this embodiment, the material of the second quantum dot ligand is n-octyl mercaptan, and the second luminescent material is a green light quantum dot solute.
[0103] The third quantum dot ligand is mixed with the quantum dots according to a fourth mixing mass ratio to form a third light-emitting material.
[0104] Among them, the material of the third quantum dot ligand is selected from one of a hydroxyl ligand, a thiol ligand and an acid ligand; in some embodiments, the hydroxyl ligand includes at least one of polyethylene glycol, polyethylene glycol-hydroxyl, glyceride, pentaerythritol ester and anhydrous sorbitan ester; the acid ligand includes at least one of decadecanoic acid, undecenoic acid, tetradecanoic acid, oleic acid and stearic acid; the thiol ligand includes at least one of n-octyl mercaptan, octadecyl mercaptan, dodecyl mercaptan and octadecyl mercaptan; in this embodiment, the material of the third quantum dot ligand is polyethylene glycol-hydroxyl, and the third luminescent material is a blue light quantum dot solute.
[0105] Among them, the fourth mixing mass ratio is in the range of (3~5):5, for example: quantum dot ligand: core-shell structure quantum dots are 3:5, 3.5:5, 4:5. According to the actual selection and specific needs, the electrophoretic mobility during electrophoretic deposition can be appropriately adjusted. In this embodiment, the fourth mixing mass ratio is preferably 4:5.
[0106] The present application can also use different quantum dot ligands to mix with quantum dots according to a fourth mixing mass ratio, so that the surface potentials of the quantum dots after they are dissolved in the solvent are different, so that the electron mobility of the quantum dots under the electric field is also different, so that in the subsequent electrophoresis process, composite films of different thicknesses that meet different optical efficiency requirements can be prepared simultaneously in the first pixel area, the second pixel area and the third pixel area, shortening the processing time of the composite film, reducing the manufacturing complexity and production cost of the composite film. Since the luminous efficiency of blue light is relatively low, the third quantum dot solute in the embodiment of the present application uses polyethylene glycol-hydroxyl with a higher polarity as a surface ligand to maximize the electron mobility of the blue light quantum dots, thereby increasing the concentration of blue light quantum dots in the composite film, thereby improving the blue light luminous efficiency of the light-emitting device.
[0107] In other embodiments, the first material solution, the second material solution and the third material solution may also be organic light-emitting solutions, and the first material, the second material and the third material include organic light-emitting materials.
[0108] In some embodiments, the organic light-emitting material includes at least one of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-C2,N)iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diaromatic anthracene derivatives, distyrene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives.
[0109] In some embodiments, the mixed solution in step S10 is formed by mixing the first material solution, the second material solution and the third material solution according to a first volume ratio, and specifically includes the following steps:
[0110] In step S12, the prepared first quantum dot solute is dissolved in the solvent to form a first material solution.
[0111] Wherein, the concentration of the first material solution is 100 mg / ml, and the first material solution is a red light quantum dot solution.
[0112] In step S12, the prepared second quantum dot solute is dissolved in the solvent to form a second material solution.
[0113] Wherein, the concentration of the second material solution is 100 mg / ml, and the second material solution is a green light quantum dot solution.
[0114] In step S12, the prepared third quantum dot solute is dissolved in the solvent to form a third material solution.
[0115] Wherein, the concentration of the third material solution is 100 mg / ml, and the third material solution is a blue light quantum dot solution.
[0116] The first material solution, the second material solution and the third material solution are mixed in a first volume ratio to prepare a mixed solution.
[0117] Among them, the first volume ratio is (1-10): (1-10): (1-10), for example: the volume of the first material solution: the volume of the second material solution: the volume of the third material solution is 1:1:5, 1:5:1, 1:5:10, 1:10:5, 5:1:10, 5:1:1, 5:5:1, 5:1:5, according to the actual selection and specific needs, according to the actual quantum dot light-emitting device The luminous efficiency of each light source can be appropriately adjusted.
[0118] In some embodiments, the volume of the third material solution is greater than the volume of the first material solution, and the volume of the third material solution is greater than the volume of the second material solution. In this embodiment, the volume of the second material solution is greater than the first material solution, and the first volume ratio is 1:5:10. After mixing according to the first volume ratio, the concentration of the first material solution in the mixed solution is 6.25 mg / ml, the concentration of the second material solution is 31.25 mg / ml, and the concentration of the third material solution is 62.5 mg / ml.
[0119] Due to the limitations of the manufacturing process, during the use of the quantum dot light-emitting device, the luminous efficiency of each color light source is blue light (19.8%), green light (21.0%), and red light (23.9%). The luminous efficiency of blue light is the lowest, the luminous efficiency of green light is second, and the luminous efficiency of red light is the highest. Therefore, the embodiment of the present application increases the volume occupied by the third material solution in the mixed solution, thereby increasing the concentration of blue light quantum dots, so as to achieve the improvement of the blue light extraction efficiency of the quantum dot film layer located in the blue light pixel area during the subsequent preparation of the quantum dot film, thereby improving the luminous efficiency of the quantum dot light-emitting device and achieving consistency in luminous performance.
[0120] In other embodiments, the luminous efficiency of each color light source can also be blue light (19.8%), red light (20.5%), and green light (23.9%), where the luminous efficiency of blue light is the lowest, followed by red light, and the luminous efficiency of green light is the highest. In other embodiments, the first volume ratio can also be 5:1:10, which increases the concentration of blue light quantum dots while increasing the concentration of red quantum dots, so as to achieve the improvement of the blue light extraction efficiency of the quantum dot film layer located in the blue light pixel area and the red light extraction efficiency of the quantum dot film layer located in the light pixel area during the subsequent preparation of the quantum dot film, thereby improving the luminous efficiency of the quantum dot light-emitting device and achieving consistency in luminous performance.
[0121] See also Figure 4 As shown, in some embodiments, the material of the substrate 1 provided in the step S30 can be glass, silicon carbide (SiC), polyimide (PI), polyethylene glycol terephthalate (PET), polycarbonate (PC), polyarylate (PAR), polyethersulfone (PES), polyethylene naphthalate two-formic acid glycol ester (PEN) or fiber reinforced plastic, which can be appropriately adjusted according to the actual situation and specific needs.
[0122] In some embodiments, a patterned electrode is formed on the substrate 1 as an anode layer 3, and the material of the anode layer 3 includes one or more of a metal, a carbon material, and a metal oxide, wherein the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb, and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene, and carbon fiber; the metal oxide includes doped or undoped metal oxides, including ITO, FTO, ATO, AZO, GZO, IZO, MZO, and AMO One or more of, or a composite electrode comprising a metal sandwiched between doped or undoped transparent metal oxides, the composite electrode comprising one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2, and appropriate adjustments can be made according to actual selections and specific needs.
[0123] In some embodiments, a hole functional layer 4 is disposed on the anode layer 3 , wherein the hole functional layer includes a hole injection layer 41 and a hole transport layer 42 which are stacked.
[0124] The material of the hole functional layer 4 includes at least one of TFB, CuPc, PVK, Poly-TPD, PFB, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS, T·APC, MCC, F4-TCNQ, HATCN, 4,4',4'-tri(N-3-methylphenyl-Nphenylamino)triphenylamine, polyaniline, transition metal oxides, transition metal sulfides, transition metal tinides, doped graphene, undoped graphene and C60, and appropriate adjustments can be made according to the actual selection and specific needs.
[0125] In this embodiment, three spaced-apart hole functional layers 4 are formed on the anode layer, and the three hole functional layers 4 are respectively disposed on the first pixel region 11 , the second pixel region 12 , and the third pixel region 13 of the substrate 1 .
[0126] See also Figure 3As shown, in some embodiments, the substrate 1 and the metal substrate 7 are electrically connected to the positive and negative electrodes of an external power supply (not shown in the figure), respectively. In this embodiment, the substrate 1 is electrically connected to the positive electrode of the external power supply, and the metal substrate 7 is electrically connected to the negative electrode of the external power supply; wherein, the first pixel area 11 is electrically connected to the positive electrode of the external power supply through the first circuit, and a first electric field is formed between the first pixel area 11 and the metal substrate 7; the second pixel area 12 is electrically connected to the positive electrode of the external power supply through the second circuit, and a second electric field is formed between the second pixel area 12 and the metal substrate 7; the third pixel area 13 is electrically connected to the positive electrode of the external power supply through the third circuit, and a third electric field is formed between the third pixel area 13 and the metal substrate 7; the first pixel area 11, the second pixel area 12 and the third pixel area 13 are all insulated from each other.
[0127] In this embodiment, the substrate 1 is electrically connected to the positive electrode of the power supply, and the metal substrate 7 is electrically connected to the negative electrode of the power supply, wherein the positive electrode of the external power supply is electrically connected to the first pixel area through a first circuit, and the first circuit is provided with a first variable resistor; the positive electrode of the external power supply is electrically connected to the second pixel area through a second circuit, and the second circuit is provided with a second variable resistor; the positive electrode of the external power supply is electrically connected to the third pixel area through a third circuit, and the third circuit is provided with a third variable resistor. In this embodiment, the positive voltage output to the first pixel area, the second pixel area and the third pixel area is changed by adjusting the resistance values of the first variable resistor, the second variable resistor and the third variable resistor, thereby changing the electric field strength of the first electric field, the electric field strength of the second electric field strength and the electric field strength of the third electric field strength.
[0128] In other embodiments, the first pixel area, the second pixel area and the third pixel area can be electrically connected to the positive poles of three power supplies respectively, wherein the first pixel area is electrically connected to the positive pole of the first power supply, the second pixel area is electrically connected to the positive pole of the second power supply, and the third pixel area is electrically connected to the positive pole of the third power supply, and the electric field strength of the first electric field, the electric field strength of the second electric field and the electric field strength of the third electric field are changed by adjusting the output voltages of the first power supply, the second power supply and the third power supply.
[0129] In some embodiments, the electric field strength of the first electric field is 1-20 V / cm; and / or
[0130] The electric field strength of the second electric field is 1 to 20 V / cm; and / or
[0131] The electric field strength of the third electric field is 1-20 V / cm.
[0132] In this embodiment, the electric field strength of the first electric field is greater than the electric field strength of the second electric field, and the electric field strength of the second electric field is greater than the electric field strength of the third electric field. For example, by respectively adjusting the resistance values of the first variable resistor, the second variable resistor and the third variable resistor, the electric field of the first electric field is 8.5V / cm, the electric field of the second electric field is 7.5V / cm, and the electric field of the third electric field is 6.5V / cm.
[0133] A uniform electric field is formed in the mixed solution so that the light-emitting material in the mixed solution is deposited on the first pixel area 11 of the substrate 1 by electrophoretic deposition to form a first composite film 21; the light-emitting material in the mixed solution is deposited on the second pixel area 12 of the substrate 1 to form a second composite film 22; and the light-emitting material in the mixed solution is deposited on the third pixel area 12 of the substrate 1 to form a third composite film 23.
[0134] In some embodiments, the duration of the electrophoretic deposition described in step S50 can be 1 to 60 seconds, for example, 1 second, 5 seconds, 10 seconds, 15 seconds, 30 seconds, 45 seconds, or 60 seconds. The duration of the electrophoretic deposition can be appropriately adjusted according to actual conditions and specific needs, and is not limited thereto.
[0135] In the embodiment of the present application, power is supplied to the first pixel area 11, the second pixel area 12, and the third pixel area 3 to form a uniform electric field with different electric field strengths between each pixel area and the metal substrate, so that the deposition rates of red quantum dots, green quantum dots, and blue quantum dots are different, so that composite films of different thicknesses can be prepared in the same time, so as to achieve the optimal optical microcavity thickness adapted to red light, green light, and blue light, shorten the processing time of the composite film, and reduce the manufacturing complexity and production cost of the composite film.
[0136] In some embodiments, in the composite film prepared in step S30, the film thickness of the first composite film is greater than the film thickness of the second composite film, and the thickness of the second composite film is greater than the film thickness of the third composite film.
[0137] In this embodiment, the step S30, after forming a first electric field between the first pixel region and the metal substrate and forming a second electric field between the second pixel region and the metal substrate so that the light-emitting material in the mixed solution is deposited on the first pixel region and the second pixel region respectively, further includes the following steps:
[0138] taking the substrate out of the mixed solution, wherein the substrate and the power source remain in a conductive state;
[0139] The substrate is immersed in a solvent, wherein the duration of immersion of the substrate in the solvent is 1 to 600 seconds, for example, 1 second, 2 seconds, 5 seconds, 10 seconds, 20 seconds, 30 seconds, 60 seconds, 120 seconds, 300 seconds, 600 seconds. The time of electrophoretic deposition can be appropriately adjusted according to actual conditions and specific needs, and is not limited here.
[0140] The soaked substrate is dried to form a composite film, wherein the drying temperature is 40°C to 250°C, for example, 40°C, 80°C, 160°C, 250°C, and the drying duration is 20 minutes.
[0141] In the embodiment of the present application, the substrate after deposition is electrically immersed, so that the residual light-emitting material and the mixed solution attached to the substrate are completely removed, thereby avoiding the doping impurities in the first composite film, the second composite film and the third composite film after drying.
[0142] Embodiments of the composite film of the present application
[0143] Based on the above-mentioned method for preparing the composite film, an embodiment of the present application further provides a composite film, which is prepared by the above-mentioned method for preparing the composite film, and specifically comprises the following steps:
[0144] Providing a mixed solution comprising a first material and a second material;
[0145] Providing a substrate and a metal substrate, placing the substrate and the metal substrate in the mixed solution, wherein the substrate is provided with a first pixel region and a second pixel region;
[0146] A first electric field is set between the first pixel area and the metal substrate to deposit the first material in the first pixel area, and a second electric field is set between the second pixel area and the metal substrate to deposit the second material in the second pixel area to form the composite film.
[0147] In some embodiments, the composite film located in the first pixel region has a different thickness from the composite film located in the second pixel region.
[0148] In the embodiment of the present application, a first pixel region, a second pixel region and a third pixel region are arranged on a substrate, and the substrate and a metal substrate are immersed in a mixed solution. After power is turned on, a uniform electric field with different electric field strengths is formed between each pixel region and the metal substrate, so that composite films of different thicknesses can be simultaneously formed on corresponding regions of the substrate by electrophoretic deposition. There is no need to perform multiple electrophoresis on the substrate, thereby shortening the processing time of the composite film and reducing the manufacturing complexity and production cost of the composite film.
[0149] Embodiments of the light emitting device of the present application
[0150] See also Figure 4 As shown, based on the above composite film and the method for preparing the composite film, the embodiment of the present application further provides a light-emitting device, including a stacked anode layer 3, a hole functional layer 4, a light-emitting layer, an electronic functional layer 5 and a cathode layer 6;
[0151] Wherein, the light-emitting layer is prepared by using the above-mentioned composite film or by the above-mentioned composite film preparation method.
[0152] In this embodiment, a first pixel region 11 , a second pixel region 12 and a third pixel region 13 are disposed on the substrate 1 , and the first pixel region 11 , the second green pixel region 12 and the third blue pixel region 13 are insulated from each other.
[0153] In some embodiments, the first pixel region 11, the second pixel region 12 and the third pixel region 13 are stacked from bottom to top with an anode layer 3, a hole injection layer 41, a hole transport layer 42, a quantum dot film layer, an electron transport layer 5 and a cathode layer 6. The quantum dot film layer corresponding to the first pixel region 11 is a first composite film 21, the quantum dot film layer corresponding to the second pixel region 12 is a second composite film 22, and the quantum dot film layer corresponding to the third pixel region 13 is a third composite film 23. The film thickness of the first composite film 21 is greater than the film thickness of the second composite film 22, and the film thickness of the second composite film 22 is greater than the film thickness of the third composite film 23.
[0154] The film thickness of the composite film in each pixel area satisfies the following formula:
[0155]
[0156] Wherein, D is the film thickness of the composite film, m is a natural number and m>0, c is the sum of the reflection phase shift between the anode layer and the cathode layer, λ is the emission wavelength of the light color in the pixel area, n is the average refractive index of the functional layer material between the anode layer and the cathode layer, and d is the sum of the thicknesses of the hole injection layer, the hole transport layer, and the electron transport layer.
[0157] Therefore, the film thickness of the first composite film 21 is:
[0158]
[0159] Among them, D R is the film thickness of the first composite film 21, λ R is the red light emission wavelength.
[0160] The film thickness of the second composite film 22 is:
[0161]
[0162] Among them, D G is the film thickness of the second composite film 22, λ G The wavelength of green light emission.
[0163] The film thickness of the third composite film 23 is:
[0164]
[0165] Among them, D B is the film thickness of the third composite film 23, λ B The wavelength of blue light emission.
[0166] Due to λ R >λ G >λ B , so D R >D G >D B .
[0167] The embodiment of the present application adopts the above-mentioned method for preparing quantum dot film layers to simultaneously prepare quantum dot film layers of different thicknesses on the first pixel area 11, the second pixel area 12, and the third pixel area 13, and the film thickness of the first composite film 21 is greater than the film thickness of the second composite film 22, and the film thickness of the second composite film 22 is greater than the film thickness of the third composite film 23, thereby simplifying the processing technology of the quantum dot light-emitting device and reducing the processing time.
[0168] In some embodiments, the material of the anode layer and / or the cathode layer includes one or more of metal, carbon material and metal oxide, the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes doped or undoped metal oxide, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or includes a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2.
[0169] In some embodiments, the hole functional layer 4 is formed on the anode layer 3. In some embodiments, the hole functional layer 4 includes a hole transport layer 41 and / or a hole injection layer 42. The materials of the hole transport layer 41 and / or the hole injection layer 42 include at least one of TFB, CuPc, PVK, Poly-TPD, PFB, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS, TAPC, MCC, F4-TCNQ, HATCN, 4,4',4'-tri(N-3-methylphenyl-Nphenylamino)triphenylamine, polyaniline, transition metal oxides, transition metal sulfides, transition metal tinides, doped graphene, undoped graphene and C60.
[0170] In some embodiments, the electronic functional layer includes an electron transport layer and / or an electron injection layer, and the materials of the electron transport layer and / or the electron injection layer include inorganic materials and / or organic materials; the inorganic materials are selected from one or more of doped or undoped zinc oxide, barium oxide, aluminum oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped elements include one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic materials include at least one of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, hydroxyquinoline compounds, polythiophene compounds, perylene imide compounds, and fullerene compounds.
[0171] Embodiment of the method for preparing the light emitting device of the present application
[0172] Based on the above light-emitting device, an embodiment of the present application further provides a method for preparing a light-emitting device, which is similar to preparing the above light-emitting device, and includes the following steps:
[0173] providing an anode layer;
[0174] preparing a hole functional layer on the anode layer;
[0175] Preparing a light-emitting layer on the hole functional layer by the composite thin film preparation method as described above;
[0176] preparing an electronic functional layer on the light-emitting layer;
[0177] A cathode is formed on the electronic functional layer.
[0178] The method for preparing a light-emitting device provided in an embodiment of the present application improves the luminous efficiency of the light-emitting device and achieves consistency in luminous performance by simultaneously preparing light-emitting layers of different thicknesses that meet different optical efficiency requirements on a first pixel region, a second pixel region, and a third pixel region.
[0179] The above scheme is further described below in conjunction with specific embodiments. The preferred embodiments of the present invention are described in detail as follows:
[0180] Embodiment 1:
[0181] (1) Providing an ITO substrate, and cleaning and drying the ITO substrate, wherein the ITO substrate is provided with a first pixel region, a second pixel region and a third pixel region.
[0182] (2) Depositing PEDOT:PSS ink on the ITO substrate to form a hole injection layer, and heating it on a heating table at 150°C for 30 minutes, wherein the thickness of the hole injection layer is 15 nm.
[0183] ⑶ Deposit TFB ink on the hole injection layer to form a hole transport layer, and heat it on a heating platform at 150° C. for 30 minutes, wherein the thickness of the hole injection layer is 30 nm.
[0184] (4) mixing the quantum dot ligand and the quantum dot material in a first mixing mass ratio of 10.3:8.7 to form a first quantum dot solute, and dissolving the mixture in a PGMEA solvent to form a first quantum dot solution,
[0185] The quantum dot ligand is PEG-COOH, and the quantum dot material is CdSe / ZnS core / shell structure quantum dots.
[0186] (5) Mixing the quantum dot ligand and the quantum dot material in a first mixing mass ratio of 4.1:5.6 to form a second quantum dot solute, and dissolving the mixture in a PGMEA solvent to form a second quantum dot solution,
[0187] The quantum dot ligand is PEG-COOH, and the quantum dot material is CdSe / ZnS core / shell structure quantum dots.
[0188] (6) Mix the quantum dot ligand and the quantum dot material in a first mixing mass ratio of 1.4:3.9 to form a third quantum dot solute, and dissolve it in PGMEA solvent to form a third quantum dot solution, wherein the quantum dot ligand is PEG-COOH and the quantum dot material is CdSe / ZnS core / shell structure quantum dots.
[0189] ⑺Mix the first quantum dot solution, the second quantum dot solution, and the third quantum dot solution in a volume ratio of 1:5:10 to form a mixed quantum dot solution.
[0190] ⑻ The first pixel area, the second pixel area and the third pixel area of the ITO substrate on which the hole transport layer is prepared are electrically connected to the positive electrode of the power supply respectively, and the metal substrate is electrically connected to the negative electrode of the power supply; wherein, the first pixel area input is 8.5V / cm, the second pixel area input is 7.5V / cm, and the third pixel area input is 6.5V / cm.
[0191] ⑼ Place the above-mentioned substrate and the metal substrate in parallel in the mixed quantum dot solution for electrophoresis for 15 seconds, wherein the thickness of the mixed first quantum dot emission film layer is 45nm, the thickness of the second mixed quantum dot emission film layer is 25nm, and the thickness of the third mixed quantum dot emission film layer is 15nm.
[0192] ⑽Take the substrate out of the mixed quantum dot solution, place it in a PGMEA solvent for washing for 10 seconds while keeping the current on, and dry it at 80°C for 5 minutes.
[0193] ⑾ Deposit ZnMgO ink on the first hybrid quantum dot emission film layer, the second hybrid quantum dot emission film layer, and the third hybrid quantum dot emission film layer to form an electron transport layer, and place it on a heating platform at 80°C and heat it for 30 minutes, wherein the thickness of the electron transport layer is 30nm.
[0194] ⑿ Depositing Ag nanomaterials on the electron transport layer through a mask to form a cathode layer, wherein the thickness of the cathode layer is 25 nm.
[0195] ⒀ Deposit NPB material on the cathode layer through a mask to form a light extraction layer, wherein the thickness of the light extraction layer is 60nm.
[0196] Embodiment 2:
[0197] The difference between this embodiment and embodiment 1 is that:
[0198] ⑷ Mix the quantum dot ligand and the quantum dot material in a first mixing mass ratio of 4:5 to form a first quantum dot solute, and dissolve it in a PGMEA solvent to form a first quantum dot solution, wherein the quantum dot ligand is PEG-COOH and the quantum dot material is a CdSe / ZnS core / shell structure quantum dot.
[0199] ⑸ Mix the quantum dot ligand and the quantum dot material in a first mixing mass ratio of 4:5 to form a second quantum dot solute, and dissolve it in PGMEA solvent to form a second quantum dot solution, wherein the quantum dot ligand is PEG-COOH and the quantum dot material is CdSe / ZnS core / shell structure quantum dots.
[0200] (6) Mix the quantum dot ligand and the quantum dot material in a first mixing mass ratio of 4:5 to form a third quantum dot solute, and dissolve it in the PGMEA solvent to form a third quantum dot solution, wherein the quantum dot ligand is PEG-COOH and the quantum dot material is CdSe / ZnS core / shell structure quantum dots.
[0201] The remaining steps are the same as those in Example 1.
[0202] Embodiment 3:
[0203] The difference between this embodiment and embodiment 1 is that:
[0204] ⑷ Mix the quantum dot ligand and the quantum dot material in a first mixing mass ratio of 4:5 to form a first quantum dot solute, and dissolve it in a PGMEA solvent to form a first quantum dot solution, wherein the quantum dot ligand is oleic acid and the quantum dot material is a CdSe / ZnS core / shell structure quantum dot.
[0205] ⑸ Mix the quantum dot ligand and the quantum dot material in a first mixing mass ratio of 4:5 to form a second quantum dot solute, and dissolve it in the PGMEA solvent to form a second quantum dot solution, wherein the quantum dot ligand is n-octanethiol and the quantum dot material is CdSe / ZnS core / shell structure quantum dots.
[0206] (6) Mix the quantum dot ligand and the quantum dot material in a first mixing mass ratio of 4:5 to form a third quantum dot solute, and dissolve it in the PGMEA solvent to form a third quantum dot solution, wherein the quantum dot ligand is PEG-COOH and the quantum dot material is CdSe / ZnS core / shell structure quantum dots.
[0207] The remaining steps are the same as those in Example 1.
[0208] Comparative Example 1:
[0209] The difference between this comparative example and Example 1 is:
[0210] After completing step (3), the first hybrid quantum dot emission film layer, the second hybrid quantum dot emission film layer, and the third hybrid quantum dot emission film layer are respectively inkjet printed in the first pixel area, the second pixel area, and the third pixel area by inkjet printing, wherein the thickness of the first hybrid quantum dot red light emission film layer is 45nm, the thickness of the second hybrid quantum dot emission film layer is 25nm, and the thickness of the third hybrid quantum dot emission film layer is 15nm.
[0211] After the preparation of the first hybrid quantum dot emission film layer, the second hybrid quantum dot emission film layer, and the third hybrid quantum dot emission film layer is completed, the preparation of the electron transport layer is directly carried out.
[0212] The remaining steps are the same as those in Example 1.
[0213] Test result analysis:
[0214] The maximum luminous efficiency (CEmax) of the light-emitting devices obtained by the preparation methods of Examples 1 to 3 and Comparative Example 1 was measured under a voltage of 6 V by a JVL efficiency tester, and the luminous brightness (L (cd / m2)) was measured by a brightness detection device. The test results are shown in Table 1 below:
[0215]
[0216] Table 1
[0217] It can be seen from the above table that the maximum luminous efficiency and luminous brightness of the light-emitting devices of the first mixed quantum dot emission film layer, the second mixed quantum dot emission film layer, and the third mixed quantum dot emission film layer prepared by the electrophoresis method are higher than those of the light-emitting devices prepared by conventional inkjet printing, and by comparing the data of Example 1 and Example 2, and Example 2 and Example 3, it can be seen that changing the type and proportion of quantum dot ligands can improve the maximum luminous efficiency and luminous brightness of the light-emitting device.
[0218] In summary, the quantum dot film layer of the light-emitting device in the embodiment of the present application is prepared by electrophoresis, which can improve the maximum luminous efficiency and luminous brightness of the light-emitting device, and the maximum luminous efficiency and luminous brightness of the light-emitting device can be further improved by changing the type and content of the quantum dot surface ligands.
[0219] Obviously, the embodiments described above are only some embodiments of the present application, rather than all embodiments. The preferred embodiments of the present application are given in the accompanying drawings, but they do not limit the patent scope of the present application. The present application can be implemented in many different forms. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive. Although the present application is described in detail with reference to the aforementioned embodiments, for those skilled in the art, it is still possible to modify the technical solutions recorded in the aforementioned specific implementation methods, or to perform equivalent replacement of some of the technical features therein. Any equivalent structure made using the contents of the specification and drawings of this application, directly or indirectly used in other related technical fields, is similarly within the scope of patent protection of this application.
Claims
1. A method for preparing a composite film, characterized in that: The following steps are involved: Providing a mixed solution comprising a first material and a second material; Providing a substrate and a metal substrate, placing the substrate and the metal substrate in the mixed solution, wherein the substrate is provided with a first pixel region and a second pixel region; A first electric field is set between the first pixel area and the metal substrate to deposit the first material in the first pixel area, and a second electric field is set between the second pixel area and the metal substrate to deposit the second material in the second pixel area to form the composite film.
2. The method for preparing a composite film according to claim 1, characterized in that: The electric field strength of the first electric field is greater than the electric field strength of the second electric field.
3. The method for preparing a composite film according to claim 1, characterized in that: The mixed solution also includes a third material solution, the volume of the third material solution is greater than the volume of the first material solution, and the volume of the third material solution is greater than the volume of the second material solution.
4. The method for preparing a composite film according to claim 3, characterized in that: The first material solution includes a first material and a solvent, the second material solution includes a second material and a solvent, and the third material solution includes a third material and a solvent, wherein the first material, the second material, and the third material are luminescent materials; The first material solution, the second material solution and the third material solution are prepared respectively by the following steps: Providing a luminescent material and a solvent, wherein the polarity of the solvent is greater than 3 Debye; The luminescent material is mixed with the solvent to form a quantum dot solution.
5. The method for preparing a composite film according to claim 4, characterized in that: The luminescent material comprises quantum dots and quantum dot ligands, and the luminescent material is prepared by the following steps: Mixing the quantum dot ligand and the quantum dot according to a first mixing mass ratio to form a first luminescent material; Mixing the quantum dot ligand and the quantum dot according to a second mixing mass ratio to form a second luminescent material; Mixing the quantum dot ligand and the quantum dot according to a third mixing mass ratio to form a third luminescent material; The first material solution, the second material solution and the third material solution are all formed by mixing quantum dot ligands and quantum dots of the same material and then mixing them with the solvent.
6. The method for preparing a composite film according to claim 5, characterized in that: The first mixing mass ratio is in the range of (3-10.3):(5-8.7); and / or The second mixing mass ratio is in the range of (3.5-4.1): (5-5.6); and / or The third mixing mass ratio ranges from (1.4 to 4): (3.9 to 5).
7. The method for preparing a composite film according to claim 6, characterized in that: The first mixing mass ratio is 10.3:8.7, the second mixing mass ratio is 4.1:5.6, and the third mixing mass ratio is 1.4:3.
9.
8. The method for preparing a composite film according to claim 4, characterized in that: The luminescent material comprises quantum dots and quantum dot ligands, and the luminescent material is prepared by the following steps: Mixing a first quantum dot ligand with the quantum dots according to a fourth mixing mass ratio to form a first light-emitting material, wherein the material of the first quantum dot ligand is selected from one of a hydroxyl ligand, a thiol ligand and an acid ligand; Mixing a second quantum dot ligand with the quantum dots according to a fourth mixing mass ratio to form a second light-emitting material, wherein the material of the second quantum dot ligand is selected from one of a hydroxyl ligand, a thiol ligand and an acid ligand; Mixing a third quantum dot ligand with the quantum dots according to a fourth mixing mass ratio to form a third light-emitting material, wherein the material of the third quantum dot ligand is selected from one of a hydroxyl ligand, a thiol ligand and an acid ligand; The first material solution, the second material solution and the third material solution are respectively formed by mixing quantum dot ligands and quantum dots of different materials with the solvent.
9. The method for preparing a composite film according to claim 8, characterized in that: The fourth mixing mass ratio ranges from (3 to 5):
5.
10. The method for preparing a composite film according to any one of claims 4 to 9, characterized in that: The luminescent material is a quantum dot luminescent material, and the quantum dot luminescent material includes at least one of a single structure quantum dot and a core-shell structure quantum dot; the material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot are respectively selected from at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, At least one of CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, At least one of PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, and the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, Al At least one of NSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; The quantum dot ligands include at least one of hydroxyl ligands, acid ligands, thiol ligands, amine ligands, (oxygen) phosphine ligands, phospholipids, phospholipids, polyvinyl pyridine, etc. The hydroxyl ligands include at least one of polyethylene glycol, polyethylene glycol-hydroxyl, glyceride, pentaerythritol ester and sorbitan ester; the acid ligands include at least one of deca-acid, undecylenic acid, tetradecanoic acid, oleic acid and stearic acid; the thiol ligands include at least one of n-octyl mercaptan, octadecyl mercaptan, dodecyl mercaptan and octadecyl mercaptan; the amine ligands include one or more of oleylamine, octadecylamine and octadecylamine; the (oxygen) phosphine ligands include at least one of trioctylphosphine and trioctylphosphine oxide; and / or The luminescent material is an organic luminescent material, and the organic luminescent material includes at least one of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-C2,N)iridium(III), 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives; and / or The material of the solvent may be selected from at least one of water, alcohol compounds, ether compounds, ester compounds and alkane compounds.
11. The method for preparing a composite film according to claim 4, characterized in that: After forming a first electric field between the first pixel region and the metal substrate and forming a second electric field between the second pixel region and the metal substrate so that the light-emitting material in the mixed solution is deposited on the first pixel region and the second pixel region respectively, the method further includes the following steps: taking the substrate out of the mixed solution, wherein the substrate remains in a conductive state with a power source; placing the substrate into a solvent for immersion; The soaked substrate is dried to form the composite film.
12. A composite film, characterized in that: The composite film is prepared by the method for preparing the composite film according to any one of claims 1 to 11, comprising: Providing a mixed solution comprising a first material and a second material; Providing a substrate and a metal substrate, placing the substrate and the metal substrate in the mixed solution, wherein the substrate is provided with a first pixel region and a second pixel region; Setting a first electric field between the first pixel region and the metal substrate so that the first material is deposited in the first pixel region, and setting a second electric field between the second pixel region and the metal substrate so that the second material is deposited in the second pixel region to form the composite film; The composite film located in the first pixel region has a different thickness from the composite film located in the second pixel region.
13. A light emitting device, characterized in that: It includes an anode layer, a hole functional layer, a light-emitting layer, an electron functional layer and a cathode layer which are stacked; Wherein, the light-emitting layer is prepared by the composite film according to claim 12 or by the method for preparing the composite film according to any one of claims 1 to 11.
14. The quantum dot light emitting device according to claim 13, characterized in that: The material of the anode layer and / or cathode layer includes one or more of metal, carbon material and metal oxide, the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes doped or undoped metal oxide, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or includes a composite electrode with a metal sandwiched between doped or undoped transparent metal oxides, the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or The hole functional layer includes a hole transport layer and / or a hole injection layer, and the material of the hole transport layer and / or the hole injection layer includes at least one of TFB, CuPc, PVK, Poly-TPD, PFB, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS, TAPC, MCC, F4-TCNQ, HATCN, 4,4',4'-tris(N-3-methylphenyl-Nphenylamino)triphenylamine, polyaniline, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped graphene, undoped graphene and C60; and / or The electronic functional layer includes an electron transport layer and / or an electron injection layer, and the materials of the electron transport layer and / or the electron injection layer include inorganic materials and / or organic materials; the inorganic material is selected from one or more of doped or undoped zinc oxide, barium oxide, aluminum oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, aluminum zinc oxide, manganese zinc oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped elements include one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material includes at least one of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, hydroxyquinoline compounds, polythiophene compounds, perylene imide compounds, and fullerene compounds.
15. A method for preparing a light-emitting device, used for preparing the light-emitting device according to claim 13 or 14, characterized in that: The following steps are involved: providing an anode layer; preparing a hole functional layer on the anode layer; Preparing a light-emitting layer on the hole functional layer by the preparation method of the composite thin film according to any one of claims 1 to 9; preparing an electronic functional layer on the light-emitting layer; A cathode layer is formed on the electronic functional layer.